2008
DOI: 10.1007/s00128-008-9484-8
|View full text |Cite
|
Sign up to set email alerts
|

DDT and HCH Isomer Levels in Soils, Carrot Root and Carrot Leaf Samples

Abstract: Agricultural cultivation assists organochlorine pesticide migration from contaminated soils to growing plants. This phenomenon is caused by retention processes that modify volatile pesticide exchange between soil, air and plants. The aim of the study was to monitor organochlorine pesticide (HCB, alpha- and gamma-HCH, pp'DDE, op'DDT, pp'DDT) levels and compare these concentrations in soil, carrot roots and carrot leaves. Fifty soil samples, 50 carrot root and 50 carrot leaf samples were taken from the same fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Although, all sites are endemic malaria communities and have agriculture as principal activity, the levels in soil and blood samples are different between communities, we do not have an explanation for those results. However, the variability of DDT levels in environmental matrices and blood samples have been reported in several studies (Yañez et al 2002;Martinez-Salinas et al 2011;Perez-Maldonado et al 2010;Waliszewski et al 2008;Zhang et al 2011). In this respect, we must point out the limitations of our assessment, as we did not study pathways such as food items (fish, meat, among others); and other environmental media (dust, sediment, air, among others) and the low number of samples in each site.…”
Section: Discussionmentioning
confidence: 81%
“…Although, all sites are endemic malaria communities and have agriculture as principal activity, the levels in soil and blood samples are different between communities, we do not have an explanation for those results. However, the variability of DDT levels in environmental matrices and blood samples have been reported in several studies (Yañez et al 2002;Martinez-Salinas et al 2011;Perez-Maldonado et al 2010;Waliszewski et al 2008;Zhang et al 2011). In this respect, we must point out the limitations of our assessment, as we did not study pathways such as food items (fish, meat, among others); and other environmental media (dust, sediment, air, among others) and the low number of samples in each site.…”
Section: Discussionmentioning
confidence: 81%
“…They were higher than total or individual organochlorine pesticide contents measured in agricultural soils in Argentina, Mexico, England and the USA in other works (Miglioranza et al, 1999;White et al, 2005;Zohair et al, 2006;Waliszewski et al, 2008) but in the same range as chlordane levels found in experiments conducted by Mattina et al (2000) in a field previously used for herbicide trials.…”
Section: Discussionmentioning
confidence: 68%
“…In their study on the uptake of organic pollutants from soil, Schroll et al (1994) found clear relationships between soil and plant contamination only in root crops. Carrots were also shown to accumulate lipophilic organochlorine pesticides as a function of soil content (Zohair et al, 2006;Waliszewski et al, 2008). However, Zohair et al (2006) found no positive correlation in potato.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As many other persistent organic pollutants (POPs), β-HCH is resistant to natural degradation, persists for several years in soils and sediments (Calvelo Pereira et al, 2006;Waliszewski et al, 2008;Abhilash and Singh, 2009) and accumulates in vegetables and animal tissues. Mammal intake of β-HCH occurs mainly through the diet and the contaminant is excreted with milk (Hanaoka et al, 2002;Lee et al, 2007;McGraw and Waller, 2009).…”
Section: Introductionmentioning
confidence: 99%